22. OVERVIEW OF CLINICAL TRIAL DESIGNS IN PRECISON ONCOLOGY (Vietnam Journal of Community Medicine, 2024)
Objective: With advancements in next-generation sequencing technology, genomics, proteomics, and metabolomics have been increasingly applied in targeted cancer therapy. This review provides an overview of clinical trial design characteristics in precision medicine for physicians, researchers, and other stakeholders involved in the implementation of clinical trials. Additionally, we summarize the global landscape of clinical trials currently underway in precision oncology.Methods: We searched PubMed from the inception until September 19, 2024 for eligible studies, which reported any clinical trial designs used in precision oncology and/or corresponding completed or on-going clinical trials.Results: A “master protocol” framework was introduced to minimize participant exposure to ineffective drugs, accelerate dug development, and lower research costs. In 2018, the FDA issued the first draft guidance to expedite oncology drug development. Within this framework, basket trials test a targeted therapy across various cancers with the same molecular alteration, while umbrella trials assess multiple therapies within a single cancer, divided by molecular profiles. Platform trials provide a flexible design to evaluate multiple treatments simultaneously against a single control. Additionally, octopus trials, adaptive trials, telescope or seamless trials, N-of-1 trials designs have been also introduced. Among 34 identified precision oncology trials, 27 studies used basket, umbrella, and platform designs, which are main designs of the master protocol framework.Conclusion: Drug efficacy assessment has gradually shifted to biomarker-guided trials, identifying many potential cancer therapies through basket, umbrella, and platform designs. Future trials may integrate technological and theoretical advancements to enhance personalized treatment and improve cancer management.
Keywords: Study design; clinical trial; precision medicine; oncology